Lentiviral gene transfer into human and murine hematopoietic stem cells: size matters. (December 2016) - Canté-Barrett, Kirsten; Mendes, Rui; Smits, Willem; Helsdingen-van Wijk, Yvette; Pieters, Rob; Meijerink, Jules
Abstract Contemporary biomedical research increasingly depends on techniques to induce or to inhibit expression of genes in hematopoietic stem cells (HSCs) or other primary cells to assess their roles on cellular processes including differentiation, apoptosis and migration. Surprisingly little information is available to optimize lentiviral transduction of HSCs. We have therefore carefully optimized transduction of murine and human HSCs by optimizing vector design, serum-free virus production and virus quantitation. We conclude that the viral RNA length, even in relatively small vectors, is an important factor affecting the lentiviral gene transfer on the level of both the virus production and the cellular transduction efficiency. Efficient transfer of large gene sequences into difficult-to-transduce primary cells will benefit from reducing the lentiviral construct size.